Inequalities in unpaid carer's health, employment status and social isolation. (12th November 2022) - Brimblecombe, Nicola; Cartagena Farias, Javiera
Abstract: Providing higher‐intensity unpaid care (higher care hours or care within the household) is associated with negative impacts on people's paid employment, mental health and well‐being. The evidence of effects on physical health is mixed and carer's social and financial outcomes have been under‐researched. The biggest evidence gap, however, is on how outcomes vary by factors other than type or level of care provision, in particular socio‐demographic factors. Our study used two waves of data (2017/19 and 2018/2020) from the United Kingdom Household Longitudinal Study for people aged 16 and older. We investigated the effects of providing care for 10 or more hours a week or within the household in interaction with people's socio‐demographic characteristics. Outcomes included mental and physical health, social isolation, employment status and earnings. We found that caring responsibilities interacted with gender, ethnicity, socio‐economic status (as measured by highest educational qualification), or age to affect carers differentially in a number of areas of their lives leading to, and exacerbating, key disadvantages and inequalities.